2015
DOI: 10.3109/09540261.2014.990421
|View full text |Cite
|
Sign up to set email alerts
|

Social media for lifelong learning

Abstract: Learning is ongoing, and can be considered a social activity. In this paper we aim to provide a review of the use of social media for lifelong learning. We start by defining lifelong learning, drawing upon principles of continuous professional development and adult learning theory. We searched Embase and MEDLINE from 2004-2014 for search terms relevant to social media and learning. We describe examples of lifelong learners using social media in medical education and healthcare that have been reported in the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 35 publications
0
29
0
3
Order By: Relevance
“…A plethora of research has convincingly shown that use of social media supplements delivery and understanding of medical education [14], lifelong learning [15], and medical professionalism [16]. The use of social media in medical education for active learning demands incorporation of scientifically designed program that should address ethics [17], facilitate group learning [18] especially at the workplace-based education [19] in an interprofessional environment [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of research has convincingly shown that use of social media supplements delivery and understanding of medical education [14], lifelong learning [15], and medical professionalism [16]. The use of social media in medical education for active learning demands incorporation of scientifically designed program that should address ethics [17], facilitate group learning [18] especially at the workplace-based education [19] in an interprofessional environment [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent work has suggested that students also voluntarily use various generalized social media platforms for their educational purposes. In particular, students select and employ social media to communicate with peer students on course‐related information (Manca & Ranierit, 2016), search for learning resources to supplement course materials (Kind & Evans, ), and seeking help from expert online users (Greenhow & Lewin, ). With easy access to knowledge shared by other users and convenient interactions with other users, the phenomenon of voluntarily using social media for formal learning appears to be a significant part of the educational landscape (Manca & Ranierit, 2016), yet research in this area is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Even though several empirical studies have been carried out on individuals' use of SNS (such as Chen (2013), Chang and Zhu (2011), Kim et al (2010), and Ridings and Gefen (2004)), very limited research has been conducted oin its use by non-profit organizations, such as professional societies. Knowledge sharing is a core process for professional societies' development (Gerken Golay et al, 2014;Kagan et al, 2015;Kind and Evans, 2015), and the use of SNS and social media is becoming very popular in these organizations (Thompson et al, 2008;Rutter and Duncan, 2011). Thus, the results of this study add value to researchers and practitioners using social networking sites in professional societies and group collaboration.…”
Section: Authormentioning
confidence: 80%
“…Thompson et al (2008) and Rutter and Duncan (2011) have acknowledged the popularity and potential of SNS and social media use by professional networks. Through illustrating examples among medical and healthcare profession, Kind and Evans (2015), indicated that learning "can be considered a social activity", and the use of online social networking and social media fosters learning through knowledge sharing, feedback, and collaboration.…”
Section: Introductionmentioning
confidence: 99%